THE INFLUENCE FACTORS ON ATHLETE’S KNEE MUSCLES STRENGHT PART I – THEORETICAL CONSIDERATIONS (GYMNASIUM, 2009)
The paper presents the factors that have an important impact on the strength of an athlete kneemuscle.The paper solves a statically approach of the equilibrium of a leg, emphasizing the major influencesof some variables, such as: body weight, angles of the leg with respect to earth, the length of a leg etc.Equation 7 is the mathematical model of the way in which the angle Φ as a function of θ and othervariables.Further geometrical conditions will allow computing the force acting on quads and knee joint, as wesee in part II.